Maternal caffeine intake during pregnancy and childhood growth and overweight: results from a large Norwegian prospective observational cohort study - Papadopoulou, Eleni (BMJ Open, 2018)
OBJECTIVES: To study the association between maternal caffeine intake during pregnancy and the child’s weight gain and overweight risk up to 8 years. DESIGN: Prospective nationwide pregnancy cohort. SETTING: The Norwegian Mother and Child Cohort Study. PARTICIPANTS: A total of 50 943 mothers recruited from 2002 to 2008 and their children, after singleton pregnancies, with information about average caffeine intake assessed at mid-pregnancy. OUTCOME MEASURE: Child’s body size information at 11 age points from 6 weeks to 8 years. We defined excess growth in infancy as a WHO weight gain z-score of >0.67 from birth to age 1 year, and overweight according to the International Obesity Task Force. We used a growth model to assess individual growth trajectories. RESULTS: Compared with pregnant women with low caffeine intake (<50 mg/day, 46%), women with average (50–199 mg/day, 44%), high (≥200–299 mg/day, 7%) and very high (≥300 mg/day, 3%) caffeine intakes had an increased risk of their child experiencing excess growth in infancy, after adjustment for confounders (OR=1.15, 95% CI 1.09 to 1.22, OR=1.30, 95% CI 1.16 to 1.45, OR=1.66, 95% CI 1.42 to 1.93, respectively). In utero exposure to any caffeine was associated with higher risk of overweight at age 3 years and 5 years, while the association persisted at 8 years, only for very high exposures. Any caffeine intake was associated with increased body mass index from infancy to childhood. Children prenatally exposed to caffeine intake >200 mg/day had consistently higher weight. Very high caffeine exposures were associated with higher weight gain velocity from infancy to age 8 years. CONCLUSION: Any caffeine consumption during pregnancy is associated with a higher risk of excess infant growth and of childhood overweight, mainly at preschool ages. Maternal caffeine intake may modify the overall weight growth trajectory of the child from birth to 8 years. This study adds supporting evidence for the current advice to reduce caffeine intake during pregnancy.